IMPLEMENTATION OF THE MOU HELSINKI ON CRIMINAL LAW POLICY IN NANGGROE ACEH DARUSSALAM (NAD) - Sekar Langit Jatu Pamungkas; Denmark Erlangga Putra; Valiantnuja Washfaa Yunandeva; Akbar Fahrudin Malik; Nur Faishal Luqman (Khairun Law Journal, 2022)
Aceh, as one of the autonomous regions in the context of the Unitary State of the Republic of Indonesia, in the practice of implementing Local Government, repeatedly not only positions the type and hierarchy of laws and regulations following Law No. 12 of 2011 on the Establishment of Laws and Regulations but also positions the Helsinki MoU as one of the legal sources. The thing that is the practice in this writing is related to how the implementation of the Helsinki MoU in criminal law policy in Aceh. Research methods are conducted with normative legal research methods and prescriptive research. Data collection in this study is done through literature research. Data analysis is done with qualitative analysis; the process of data analysis and using legal data is also possible to use non-legal data. This study showed that after the MoU of peace between the Indonesian government and GAM was marked on August 15, 2005, in Helsinki, Finland, 24 governments then passed Law No. 11 of 2006 on the aceh government. This law is a political commitment of the Indonesian government in following up on the results of the peace agreement in Helsinki. One of the authorities (autonomy/self-government) granted in the law is to implement Islamic sharia in Aceh in a kaffah both in terms of worship, education, muamalat, shiar, civil law, and criminal law. While implementing the Helsinki MoU is, the regulation related to Jinayat (Criminal Law) has strengthened. Other judicial institutions are also concerned about implementing criminal law in Aceh, although the rules about Criminal Law still cause debate.